Trauma outcomes at higher-level trauma centres compared with lower-level trauma centres: a systematic review and meta-analysis - Jayakumar, Nithish; Sarhan, Islam; Lahart, Ian M.; Athar, Sajjad; Neil Ashwood (International Journal of Research in Orthopaedics, 2024)
The introduction of trauma systems has helped reduce mortality in severely injured patients. This fall in mortality, however, appears to be concentrated in higher-level trauma centres (TCs) in comparison to lower-level TCs, but the evidence is inconsistent. Therefore, we undertook a systematic review with the aim of comparing outcomes in lower-level TCs (i.e. level III and IV trauma centres) with higher-level TCs (i.e. level I and II centres). This systematic review was performed in accordance with the guidelines defined in the preferred reporting items for systematic reviews and meta-analyses statement (PRISMA). The review was registered on PROSPERO (CRD42019111933). Mortality data were combined using the Mantel-Haenszel random-effects method for meta-analysis, using Review Manager (RevMan v5.3.5). We found 28 eligible articles from an initial total of 10,816 identified abstracts. Our meta-analysis revealed no evidence of a difference in mortality risk in severely injured patients between lower-level and higher-level TCs (RR 1.55; 95% CI 0.97 to 2.50; p=0.07), but there was considerable heterogeneity (I2=92%) in the dataset. The risk of death in lower-level TCs in patients with neurological trauma, however, was statistically lower than in higher-level TCs (RR 0.80; 95% CI 0.73 to 0.86; I2=78%; p<00001). There was a higher risk of death in patients with neurological trauma managed at higher-level TCs and this is likely to be due to the higher severity of injury (intracranial and extracranial) sustained by patients at higher-level TCs. However, the high level of heterogeneity in the risk estimates of evaluated studies reduces the certainty of our interpretations.